The procedure of evaluating the quality of accounting software - Вольська, Катерина Олександрівна (Problems of Theory and Methodology of Accounting, Control and Analysis, 2019)
The article gives an overview of literary sources regarding the issues of software efficiency and reliability; analyzes international standards that regulate the qualitative characteristics of software products at different stages of their life cycle. The division of software quality criteria into general and special ones, in particular, for accounting software products, has been made. The problems of software selection by the officials of the enterprise, which do not have special knowledge in the field of programming, have been updated, and proposals for solving this problem are presented, namely, it is proposed to evaluate software for accounting in two directions: 1) before purchasing and 2) during the process of working with it. The author has determined that quality is more important to users when software is used, because it is the user’s perceived quality of the medium containing the software, it is determined by the results of the use of the software in the environment, and not by its properties as such. A system of criteria and indicators is developed that will help to select a software product depending on the needs of the business entity and its management. The article states that when choosing a quality software product, it is first of all to determine what is necessary in the subject of business, which are volumes, business turnover, how accounting is carried out, how the accounting information will be stored, or whether it is necessary to acquire software product, how the program product is maintained by its developers, etc.